Innovative Learning Media for Interior Design using Augmented Reality at Vocational High Schools - Sahria, Yoga; Santoso, Budi; Kuat, Tri (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
One aspect of the concept of building design development is interior design. The accuracy of the placement of interior materials is very important for (SMK) students majoring in Building Drawing Engineering. However, it may be difficult to present and organize material in real life. This barrier can be caused by a lack of materials or the ability to see objects from multiple angles. To realize the Vocational Center of Excellence and SMK Bisa programs, augmented reality technology is present as a solution in vocational education. Augmented reality is a technology that allows virtual things to be placed in the real world. The reason for choosing this research topic is that users can interact with virtual things in an augmented reality environment providing them with hands-on experiences. Objects that are displayed in the form of interior materials can be in 3D so that they look as close as possible to the original object. Users can interact and change the location of interior materials directly and realistically using augmented reality applications. The method used in this research is the Lee & Owens Development Model starting from Assessment/analysis, Need assessment, front-end analysis, design, development, Implementation, and Evaluation. The application developed only includes some interior design materials, Design markers have a high level of augmentability, so users will be able to immediately see a 3D model when the marker is scanned, The application has been tested on several smartphones and the results are successful